2021
DOI: 10.3389/fimmu.2021.773570
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenosine RNA Modification in the Tumor Immune Microenvironment: Novel Implications for Immunotherapy

Abstract: N6-methyladenosine (m6A) methylation is one of the most common modifications of RNA in eukaryotic cells, and is mainly regulated by m6A methyltransferases (writers), m6A demethylases (erasers), and m6A binding proteins (readers). Recently, accumulating evidence has shown that m6A methylation plays crucial roles in the regulation of the tumor immune microenvironment, greatly impacting the initiation, progression, and metastasis processes of various cancers. In this review we first briefly summarizes the m6A-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 149 publications
(234 reference statements)
0
23
0
Order By: Relevance
“…Specific depletion of METTL3 leads to impaired phenotypic and functional maturation of DCs and reduced expression of co-stimulatory molecules CD40, CD80 and cytokine IL-12 involved in maturation. Silencing of METTL3 has been shown to reduce the ability of DCs to stimulate T-cell responses [ 24 ]. Moreover, METTL3-mediated methylation of CD40, CD80 and TLR4 signal transduction junction TIRAP transcripts promotes translation in DCs to stimulate T-cell activation and enhances TLR4/NF-κB signaling to promote cytokine production [ 126 ].…”
Section: A Methylation Remodels Immunosuppressive Tme By Directly Aff...mentioning
confidence: 99%
See 1 more Smart Citation
“…Specific depletion of METTL3 leads to impaired phenotypic and functional maturation of DCs and reduced expression of co-stimulatory molecules CD40, CD80 and cytokine IL-12 involved in maturation. Silencing of METTL3 has been shown to reduce the ability of DCs to stimulate T-cell responses [ 24 ]. Moreover, METTL3-mediated methylation of CD40, CD80 and TLR4 signal transduction junction TIRAP transcripts promotes translation in DCs to stimulate T-cell activation and enhances TLR4/NF-κB signaling to promote cytokine production [ 126 ].…”
Section: A Methylation Remodels Immunosuppressive Tme By Directly Aff...mentioning
confidence: 99%
“…To overcome these barriers, systematic evaluation of the phenotypic and functional changes of immune cells in TME is crucial. Interestingly, increasing evidence suggests that m 6 A methylation has the potential to support tumor immune escape via modulation of the immunosuppressive TME [ 22 24 ]. Indeed, tumor cell proliferation leads to hypoxia, which promotes the onset of metabolic reprogramming and participates in the phenotypic and functional conversion of immune cells in a m 6 A methylation-dependent manner, leading to the formation of an immunosuppressive tumor microenvironment (TME) that facilitates changes in mutually supportive biological functions to stimulate distant tumor metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence has demonstrated that m6A modifications are involved in tumor immunity [ 22 ]. For the purpose of further analyzing the association between m6A modifications and the TME, we investigated the association of 21 m6A gene expression profiles with the infiltration of 22 distinct immune cell types.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have linked m6A modifications to the regulation of tumor immunity and response to ICIs [ 22 ]. To date, accumulating reports have shown the crucial roles of m6A regulators in carcinogenesis, development, diagnosis, therapy, and prognosis [ 21 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation